High SHP2 expression determines the efficacy of PD‐1/PD‐L1 inhibitors in advanced KRAS mutant non‐small cell lung cancer. Issue 19 (6th September 2021) - Feng, Hui‐Bo; Chen, Yu; Xie, Zhi; Jiang, Jie; Zhong, Yu‐Min; Guo, Wei‐Bang; Yan, Wen‐Qing; Lv, Zhi‐Yi; Lu, Dan‐Xia; Liang, Hong‐Ling; Xu, Fang‐Ping; Yang, Jin‐Ji; et al.
Abstract: Background: Src homology region 2 domain‐containing phosphatase 2 (SHP2) is a novel target for Kirsten rat sarcoma oncogene (KRAS) mutant cancer. We retrospectively studied the significance of SHP2 in KRAS mutant non‐small cell lung cancer (NSCLC) treated with immunotherapy and its relationship with tumor microenvironment (TME). Methods: Sixty‐one advanced KRAS mutant NSCLC patients who underwent immunotherapy were enrolled. Next‐generation sequencing (NGS) was used to profile mutation status. The expression of SHP2, phospho‐SHP2 (pSHP2), and programmed death ligand 1 (PD‐L1) were analyzed by immunohistochemistry (IHC). Quantitative multiplexed immunofluorescence cytochemistry (mIFC) analysis was conducted to describe the TME. Results: SHP2 was heterogeneously expressed in 32 samples in both tumor cells and immune cells and highly expressed (H‐score >10) in 25 (78.1%) samples. The expression levels of SHP2 and pSHP2 were positively correlated. Stromal SHP2 (s‐SHP2) was higher in tumors with PD‐L1 ≥50% versus PD‐L1 <50% ( p = 0.039). By quantitative mIFC analysis, the expression of s‐SHP2 had positive correlation with CD8, CD4, CD68, and PD‐L1 levels in stromal area. Patients with high SHP2 expression made up 100.0% of the partial respond (PR) and 80.0% of the stable disease (SD), whereas 50.0% of the progress disease (PD). High SHP2 expression was associated with longer progression‐free survival (PFS) and overall survival (OS) ( p < 0.001, p = 0.013). Patients with high expression of both SHP2 and PD‐L1 had longer PFS ( p < 0.001). Conclusion: High SHP2 expression could predict the efficacy of immunotherapy and better survival in advanced KRAS mutant NSCLC. SHP2 may function in both tumor cells and immune cells, warranting further study on the potential diverse effects of SHP2 inhibition in TME. Abstract : SHP2 was heterogeneously expressed in both tumor cells and immune cells in KRAS mutant NSCLC. ICI can benefit more in patients with high SHP2‐expressed NSCLC. High level of SHP2 was associated with better PFS and OS, suggesting SHP2 is a promising marker to predict the efficacy of ICI and better survival for KRAS mutant NSCLC.